Development of Clove (Syzygium aromaticum) and Cinnamon (Cinnamomum burmannii) Based Food Sanitizer - Kam, Natania; Joanina, Mikaela; Hardoko, Hardoko; Rosa, Dela; Halim, Jeremia Manuel (Universitas Sebelas Maret, 2023)
Although minimally processed food contains more beneficial nutrients, it is one of the largest sources of food-borne diseases. Therefore, this research aims to develop the efficiency of food sanitizer, targeted toward fresh food products using a green chemistry approach. The cinnamon and clove were extracted using water distillation and ethanol extraction with the green technique. The extracts were characterized for antimicrobial activity and incorporated into basic food sanitizer formulation. The solution's color and stability were evaluated and the sanitizer was applied to decontaminate fresh strawberries. The total microbial load before and after the application was also compared to determine the effectiveness of the food sanitizer. Based on the results, all the extracts showed high effectiveness in inhibiting various spoilage microorganisms that exist in food produced with water distillation. The extracts also showed better ability when incorporated into a water-based sanitizer. All the developed food sanitizers can reduce the microbial load of the fresh produce by 4 log per 5 minutes of contact time. Meanwhile, the water-distilled clove extract showed the most effectiveness, decreasing microbial log by 3.93±0.07 log CFU g-1 of bacteria load and 4.37±0.14 log CFU g-1 of mold load, respectively which performed good dispersion stability for approximately 10 days of observation. This indicated that food sanitizer using water-distilled clove extract could be applied as a good alternative to chemical-based sanitizer.